Measuring mixed-use transformations in residential buildings of cairo$1 (Bs old neighborhoods (the case of zamalek and heliopolis (montaza division) :s mapping, assemblage thinking, mxi, entropy, preliminary threshold indicators - Ghada Mohamed Ahmed Attia; Tarek Abdel Latif Aboul Atta (2024)
The study meticulously examines the ground-floor activities in Zamalek and Heliopolis (Motaza division), shedding light on their physical and economic features. The research provides an empirical diagnostic of urban characteristics for both neighborhoods through comprehensive field surveys, assemblage-thinking, mapping, indexing and measuring imbalances both neighborhoods through MXI and Entropy. The study also introduces a preliminary novel approach, a threshold indicator tool for detecting saturation of mixed-use activities by detecting relationship between closed shops phenomenon and entropy and FSI.
(3JJYeb gPg GdCWQhMI aj JMhjd GKfJjf ef VhGMj GdbGgQI GdJj cGfJ PGJ jhe eLJeYGJ MOGFbjI Edi eLJeYGJ UGNHI eJYOOI GdESJNOGeGJ(B. (3JOQS GdOQGSI HObI CfTWI GdWGHb GdCQVj aj GdReGdc heUQ GdLOjOI (B((3bSe GdefJRdI(B)(3, hJSdW GdVhA Ydi NUGFUgG GdeGOjI hGdEbJUGOjI(B. (3ef NdGd fgL TGed jJVef GdeShMGJ GdejOGfjI ef NdGd GdJacjQ GdJLejYj hQSe GdNQGFW hGdagQSI hbjGS GdENJdGdGJ h jhaQ GdHMK JTNjUG JLQjHjG ddNUGFU GdMVQjI dcdG GdMjjf(B. (3JbOe GdOQGSI fgLG ChdjG COGI eDTQ MOjI ddcTa Yf JTHY GdCfTWI eJYOOI GdESJNOGeGJ , ef NdGd JMdjd GdYdGbI GdMGdjI Hjf XGgQI GdeJGLQ GdeZdbI h GdCfJQhHi h GdcKGaI GdHfGFjI(B. (3hgPg GdfJGFL HeKGHI COGI bjeI ddeNWWjf GdMVQjjf hGdHdOjGJ, hJbOe EQTGOGJ ddfeh GdeSJbHdj aj GdCMjGA GdbOjeI aj GdbGgQI(B.s
Thesis (Ph.D)-Cairo University, 2024.
Bibliography: pages 153-158.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Architectural Engineering; Assemblage -- MXI -- Entropy -- Floor Space Index -- Threshold Indicators